Sportivnye dostiženija v tolkanii jadra u vedušcich atletov Rossijskoj Federacii: trechletnjaja dinamika i kolebanija rezul'tatov v každom sezone - Loktev, S. A.; Shubin, M. S.; Chernukha, S. M.; Popov, N. I. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
The work analyzes the three-year competitive activity of the leading domestic shot putters to identify the risk factors for reducing the level of sports achievements of an organizational nature that are not related to the content of the training process. 252 sports results of the leading domestic putters and 202 results of the leading foreign athletes for the period 2013-2015 were analyzed. Foreign athletes showed a significantly higher level of sporting achievements compared to domestic athletes. The average age of the leading domestic pushers of the nucleus does not differ significantly from that of the leading foreign athletes, which excludes the age difference as one of the reasons for the lag. One of the factors that can have a negative impact on the average group and average individual level of sporting achievements among domestic athletes is a much larger total number of starts for the season, primarily winter ones. The leading domestic shot putters have a distinct tendency to lesser sports achievements in the second half of the summer season, which may be due to the state of hidden overtraining. In addition, there is a pronounced trend towards a decrease in results in foreign starts, which indicates an insufficient level of psychological stability.